Heterochrony as Diachronically Modified Cell-Cell Interactions - John S. Torday (Biology, 2016)
Heterochrony is an enabling concept in evolution theory that metaphorically captures the mechanism of biologic change due to mechanisms of growth and development. The spatio-temporal patterns of morphogenesis are determined by cell-to-cell signaling mediated by specific soluble growth factors and their cognate receptors on nearby cells of different germline origins. Subsequently, down-stream production of second messengers generates patterns of form and function. Environmental upheavals such as Romer’s hypothesized drying up of bodies of water globally caused the vertebrate water-land transition. That transition caused physiologic stress, modifying cell-cell signaling to generate terrestrial adaptations of the skeleton, lung, skin, kidney and brain. These tissue-specific remodeling events occurred as a result of the duplication of the Parathyroid Hormone-related Protein Receptor (PTHrPR) gene, expressed in mesodermal fibroblasts in close proximity to ubiquitously expressed endodermal PTHrP, amplifying this signaling pathway. Examples of how and why PTHrPR amplification affected the ontogeny, phylogeny, physiology and pathophysiology of the lung are used to substantiate and further our understanding through insights to the heterochronic mechanisms of evolution, such as the fish swim bladder evolving into the vertebrate lung, interrelated by such functional homologies as surfactant and mechanotransduction. Instead of the conventional description of this phenomenon, lung evolution can now be understood as adaptive changes in the cellular-molecular signaling mechanisms underlying its ontogeny and phylogeny.